On fractal FSS suitable for WLAN and WiMAX communication. Issue 7 (July 2015) - Ray, Arup; Kahar, Manisha; Sarkar, Debashree; Sarkar, P. P.
ABSTRACT Multiband properties of three different types of fractals namely Sierpinski Carpet, Koch Snowflake, and Sierpinski Gasket have been exploited. It is seen that all three fractal frequency selective surfaces (FSSs) on suitable optimization of their fractal geometry exhibit dual band properties of wireless local area network (WLAN), IEEE 802.11b standard, but at the fatal cost of large electrical size. In an attempt of making their size less, the Sierpinski Carpet and Koch Snowflake fractal looses their resonance properties partially at WLAN frequencies; however, the newly designed, modified Sierpinski Gasket FSS, marvelously exhibits stable resonance at WLAN frequencies with an additional resonance at WiMAX frequency, IEEE 802.16e standard. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1546–1550, 2015